Low-Complexity Relay Selection for Full-Duplex Random Relay Networks - Jonghyun Bang; Taehyoung Kim (Mathematics)
Full-duplex relay networks have been studied to enhance network performance under the assumption that the number and positions of relay nodes are fixed. To account for the practical randomness in the number and locations of relays, this paper investigates full-duplex random relay networks (FDRRNs) where all nodes are randomly distributed following a Poisson point process (PPP) model. In addition, we propose a low-complexity relay selection algorithm that constructs the candidate relay set while considering the selection diversity gain. Our simulation results demonstrate that, rather than simply increasing the number of candidate relay nodes, selecting an appropriate candidate relay set can achieve significant performance enhancement without unnecessarily increasing system complexity.